2009
DOI: 10.1080/15622970802480905
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation in a patient with therapy-resistant major depression

Abstract: Transcranial direct current stimulation (tDCS) of the prefrontal cortex (PFC) has been reported to exert significant antidepressant effects in patients with major depression. Several recent studies found an improvement of depressive symptoms in drug-free patients. Here we report the case of a 66-year-old female patient suffering from recurrent major depressive episodes who underwent anodal tDCS of the left dorsolateral PFC over 4 weeks as an add-on treatment to a stable antidepressant medication. Only a modest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 11 publications
2
13
0
2
Order By: Relevance
“…Palm et al [115] found improvement on the Hamilton Depression Rating Scale (HDRS) of 16 % with 1 mA tDCS and 25 % with 2 mA tDCS in a subsample of 14 geriatric patients (mean age 68.22 years, range [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] although this is in line with findings from their larger study sample. Palm et al [116] also reported a case study of a 66-year-old female, who had no mood improvements after a course of tDCS but nonetheless showed improvements in verbal fluency (1 mA, 20 min, 16 sessions over 27 days).…”
Section: Transcranial Direct Current Stimulation (Tdcs)mentioning
confidence: 98%
“…Palm et al [115] found improvement on the Hamilton Depression Rating Scale (HDRS) of 16 % with 1 mA tDCS and 25 % with 2 mA tDCS in a subsample of 14 geriatric patients (mean age 68.22 years, range [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] although this is in line with findings from their larger study sample. Palm et al [116] also reported a case study of a 66-year-old female, who had no mood improvements after a course of tDCS but nonetheless showed improvements in verbal fluency (1 mA, 20 min, 16 sessions over 27 days).…”
Section: Transcranial Direct Current Stimulation (Tdcs)mentioning
confidence: 98%
“…Depuis cette date, 10 études cliniques randomisées et contrôlées par placebo [12,13,[19][20][21][22][23][24][25][26] (Tableau 1), 8 études ouvertes [27][28][29][30][31][32][33][34] (Tableau 2) et 6 cas cliniques [35][36][37][38][39][40] ont été publiés. Les patients inclus variaient beaucoup en fonction des traitements médicamenteux associés, de la résistance au traitement ou du caractère uni-ou bipolaire de la dépres-sion.…”
Section: Résultatsunclassified
“…Cependant, d'autres études n'ont pas retrouvé ce type d'améliorations [22][23][24]27,30]. Par ailleurs, quelques cas cliniques d'amélioration de la fluence verbale après traitement par tDCS ont été rapportés dans des contextes de dépression résistante [35] ou post-accident vasculaire céré-bral [39].…”
Section: Efficacité De La Tdcsunclassified
“…The available case reports for tDCS in depression fall into three scenarios: (1) report of emergent hypomanic/manic symptoms following tDCS [46][47][48][49] ; (2) description of tDCS use in a specific type of depression (post-stroke depression) 50 and (3) evaluation of clinical symptoms and EEG findings in a patients with treatment-resistant depression 51 (Table 3).…”
Section: Case Reportsmentioning
confidence: 99%